Genomic Diversity Analysis of SARS-CoV-2 and Epidemiological Features of Adaptation of COVID-19 Agent to Human Population (Communication 1) - Ya. M. Krasnov; A. Yu. Popova; V. A. Safronov; A. V. Fedorov; D. V. Badanin; S. A. Shcherbakova; V. V. Kutyrev (Проблемы особо опасных инфекций, 2020)
Objective: to study the evolution of SARS-CoV-2 virus in the process of adapting to human organism duringthe current pandemic.Materials and methods. Database (GISAID) on nucleotide sequences of SARS-CoV-2 virus genome, obtained from clinical samples during the period of late December, 2019–July, 2020. Phylogenetic tree diagram construction was carried out applying BioNumerics v.7.6 software using Maximum parsimony algorithm.Results and discussion. The most substantial change in the genomes of SARS-CoV-2 virus are associated one-time mutations in ORF1b (P314L) and S (D614G) genes, as a result of which the overwhelming majority of identified isolates of this virus have the stated pair of substitutions to date. Many researches link the substitution in S (D614G) gene to the decreased pathogenicity in the strains that contain it, which may be also explained by enhanced methodology of patient treatment in the course of pandemic. The effect of the mutation in ORF1b (P314L) gene has not yet been investigated. P314L and D614G mutations are closely related and only their combined presence in the genome favored the dissemination of the genovariants of SARS-CoV-2 virus. Analysis of congregated epidemiological data testifies to the fact that the spread of new genovariants may be associated with biological properties facilitating human-to-human transmission. Thereat, associated decrease in lethality may reflect not only advancements in methods of treatment, but possible attenuation of virulent properties. Thus, observed growth in dissemination potential against the background of decrease in virulence is, probably, one of the forms of adaptation of new coronavirus to human population and, apparently, will remain in the future as the integration of SARS-CoV-2 virus into the structure of seasonal ARVI agents.